The comparative study of general intelligence and scholastic in urban, highland and coastal students - Dewi, Rosmala; Dalimunthe, Raudah Zaimah; Putri, Utami Nurhafsari; Harmen, Hilma; Dalimunthe, Muhammad Bukhori (Intelektual Pustaka Media Utama, 2025)
This study aims to determine: i) differences in general intelligence students in the urban, highland, and coastal, ii) scholastic differences students in the urban, highland and coastal, and iii) the relationship of general intelligence and scholastic students urban, highland and coastal. Samples were taken by using purposive sampling techniques as many as 670 students from the urban, 764 people from the highland and 604 students from the coastal. Analysis data used descriptive analysis, analysis of variance followed by Tukey honestly significant difference (HSD) analysis, and regression. The results showed that 31.4% of students in the highland have a general intelligence above the average of their age students, while students who live in the urban with a general intelligence above average age is only 23.3%, while on the coastal is only 8.1%. It was found that; i) there are differences in general intelligence of students, ii) there are differences in scholastic ability of students, and iii) there is a general intelligence effect to scholastic ability students in the urban, highland and coastal.